Project risk management for underground project - Ng, Junyang (2014)
This Final Year Report covers the analysis of underground tunnelling projects and develops a framework to compare the difference in the costs and time with the change of factors. The tunnelling methods that are focused on are the Drill & Blast method and Tunnel Boring Machine (TBM) method. Risk management process and the different types of risks are being discussed to provide a better understanding of the risk assessment process. The geological parameters such as the RMR rating and Q-value parameters are used to determine geological conditions. Two actual projects, one from each tunnelling method, are being compared and analysed based on cost and time to model a cost estimation guideline. The costs are based on general factors such as labour, equipment and supplies, and other miscellaneous costs. The cost estimation model is created by extracting real time data, and can be used as future reference in tunnelling projects. These data can be used as a reference in conjunction with future projects to produce an efficient cost estimation strategy.